Role of Trichoderma harzianum in mitigating NaCl stress in Indian mustard (Brassica juncea L) through antioxidative defense system - Ahmad, Parvaiz; Hashem, Abeer; Abd-Allah, Elsayed Fathi; Alqarawi, A. A.; John, Riffat; Egamberdieva, Dilfuza; Gucel, Salih (Frontiers in Plant Science, 2015)
Salinity stress affected crop production of more than 20% of irrigated land globally. In the present study the effect of different concentrations of NaCl (0, 100 and 200 mM) on growth, physio-biochemical attributes, antioxidant enzymes, oil content, etc in Brassica juncea and the protective role of Trichoderma harzanium (TH) was investigated. Salinity stress deteriorates growth, physio-biochemical attributes, that ultimately leads to decreased biomass yield in mustard seedlings. Higher concentration of NaCl (200 mM) decreased the plant height by 33.79%, root length by 29.79% and plant dry weight (DW) by 34.50%. On the other hand, supplementation of TH to NaCl treated mustard seedlings showed elevation by 13.81%, 11.83% and 16.76% in shoot, root length and plant DW respectively as compared to plants treated with NaCl (200 mM) alone. Oil content was drastically affected by NaCl treatment; however, TH added plants showed enhanced oil percentage from 19.35% to 23.44% in the present study. NaCl also degenerate the pigment content and the maximum drop of 52.00% was recorded in Chl. ‘a’. Enhanced pigment content was observed by the application of TH to NaCl treated plants. Proline content showed increase by NaCl stress and maximum accumulation of 59.12% was recorded at 200 mM NaCl. Further enhancement to 70.37% in proline content was recorded by supplementation of TH. NaCl stress (200 mM) affirms the increase in H2O2 by 69.57% and MDA by 36.56%, but reduction in the accumulation is recorded by addition of TH to mustard seedlings. 200 mM NaCl elevated SOD, POD, APX, GR, GST, GPX, GSH and GSSG by 31.17%, 43.15%, 26.25%, 29.78%, 40.07%, 31.81%, 42.26% and 64.50% respectively. Further enhancement was observed by the application of TH to the NaCl fed seedlings. NaCl stress suppresses the uptake of important elements in both roots and shoots, however addition of TH restored the elemental uptake in the present study. Mustard seedlings treated with NaCl and TH showed restricted Na uptake as compared to seedlings treated with NaCl alone. In conclusion, TH proved to be very beneficial in imparting resistance to the mustard plants against NaCl stress through improved uptake of essential elements, modulation of